Magmatic, metamorphic and structural history of the Variscan Lizard ophiolite and metamorphic sole, Cornwall, UK - Mackay‐Champion, TC; Searle, MP; Tapster, S; Roberts, NMW; Shail, RK; Palin, RM; Willment, GH; Evans, JT (Wiley, 2024)
The Lizard ophiolite, Cornwall, South-West England, is the largest and best-preserved ophiolite within the Variscan orogenic belt. It forms part of the Rheic-Rhenohercynian suture zone, and was obducted northwestward onto the passive continental margin of Avalonia (Laurussia) during the Middle Devonian. It comprises an almost complete thrust slice of oceanic crust with sheeted dykes, gabbros, Moho transition sequence, and upper-mantle peridotites, underlain by a metamorphic sole. Despite the importance of the Lizard ophiolite in understanding Variscan tectonics, the origin and age of the Lizard ophiolite are debated. We present new field observations, structural maps and cross-sections of the Lizard ophiolite from extensive re-mapping, integrated with U–Pb geochronology, petrology, thermobarometry, and whole rock geochemistry. We report new U–Pb zircon (CA-ID-TIMS and LA-ICPMS) ages of 386.80 ± 0.25/0.31/0.52 Ma (Givetian) from a plagiogranite dyke intruding the Crousa Gabbros at Porthoustock, and 395.08 ± 0.14/0.22/0.47 Ma (Emsian) from partial melts of the metamorphic sole Landewednack Amphibolites at Mullion Cove. These ages, respectively, precisely date the formation of the Lizard ophiolite oceanic crust, and the age of cooling post peak-metamorphism of the sole. Petrological modeling on the Landewednack Amphibolites suggests peak metamorphic conditions of 10 ± 2 kbar and 600 ± 75°C. We demonstrate that the Lizard ophiolite formed as a supra-subduction zone ophiolite overlying an inverted metamorphic sole, and we combine our observations and data into a new geodynamic model for the formation and obduction of the ophiolite. The current data supports an induced subduction initiation model.